Emergency nurses ‘ job satisfaction and its determinants - Forouzanfar, Mohammad Mehdi; Alitaleshi, Hesam; Hashemi, Behrooz; Baratloo, Alireza; Motamedi, Maryam; Majidi, Alireza; Rahmati, Farhad; Safari, Saeed (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim: Job satisfaction and its effective factors is an important issue in prodctivity improvement.The main purpose of this study is evaluation of Job satisfaction and its effective factors in three teaching hospitals of Shahid Beheshti University of medical sciences. Materials and Methods: In this cross sectional study, 100 nurses in three general hospitals were questioned ragarding Brayfield-Rothe job satiafactin questionare. Finnaly demographic and professional data as well as responses to questionair were analysed according to level of satisfaction and its effective factors. Findings: Ninty nurses were answerd to questionair (78.9% female). The mean age of respondents was 28.8 ± 4.9 years. The mean level of job satisfaction was 54.6 ± 12.1 based on Brayfield-Rothe criterias. There is a direct relationship between job satisfaction and monthly income. Conclusion: 64% of emergency nurses had job satisfaction based on Brayfield-Rothe criterias. It seems that income satisfaction in compare with other effective factors play a significant role in job satisfaction Key words: Job satisfaction, nursing service, emergency department.